Implementasi Asesmen Merdeka Belajar pada Madrasah Aliyah Negeri di Pekanbaru: Studi Kasus dan Evaluasi - Mohd Fauzan; Rafiqi Almunawwar; Khusnal Marzuqo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the implementation of the Merdeka Belajar (Independent Learning) assessment policy in State Islamic Senior High Schools (Madrasah Aliyah Negeri or MAN) in Pekanbaru. The Merdeka Belajar assessment emphasizes a holistic evaluation approach, focusing on competency development and aligning with students' needs and potentials. Employing a qualitative approach with a case study method, data were collected through observations, interviews with teachers and school principals, and analysis of assessment documents utilized in the madrasahs. The findings reveal that the implementation encompasses various strategies, including flexible formative assessments, the use of diagnostic assessments to identify students' learning needs, and summative assessments presented not only in the form of tests but also as projects and portfolios. Nonetheless, several challenges persist, such as varying levels of teacher understanding regarding the Merdeka Belajar assessment concept, limited supporting infrastructure, and the necessity for ongoing professional development to ensure effective implementation. Therefore, comprehensive policies and sustained support are essential to enable the Merdeka Belajar assessment to significantly enhance the quality of learning in madrasah.